The Financial Technology: Meningkatkan Inclusif Financial Emkm Di Era Pandemi Covid-19 - Jamaluddin Majid (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to find out how the role of financial technology (fintech) in realizing financial inclusion for micro, small and medium-sized entities (EMKM) during the covid-19 pandemic which is currently endemic. The research method applied in this paper is a qualitative method by collecting data through literature study. The results of the study indicate that the Covid-19 pandemic indirectly affects the increase in the use of technology, including in the financial sector, by using fintech. In addition, Fintech provides easy access to various types of financial services, can reach all EMKM to remote areas, opens easier and faster access to business financing, and contributes to EMKM empowerment and the local economy in increasing EMKM financial inclusion.